Existence and Continuous Dependence on Initial Data of Solution for Initial Value Problem of Fuzzy Multiterm Fractional Differential Equation. (19th June 2019) - Choi, Huichol; Sin, Kinam; Pak, Sunae; So, Sungryol
Abstract : In this paper, the fuzzy multiterm fractional differential equation involving Caputo-type fuzzy fractional derivative of order0 < α < 1 is considered. The uniqueness of solution is established by using the contraction mapping principle and the existence of solution is obtained by Schauder fixed point theorem.